The Mexican Social Protection System in Health - Bonilla-Chacín, M.E.; Aguilera, Nelly (World Bank, Washington DC, 2013)
With a population of 113 million and a per-capita Gross Domestic Product, or GDP of US$10,064 (current U.S. dollars), Mexico is one of the largest and highest-income countries in Latin America and the Caribbean (LAC). The country has benefited from sustained economic growth during the last decade, which was temporarily interrupted by the financial and economic crisis. Real GDP is projected to grow 3.8 percent and 3.6 percent in 2012 and 2013, respectively (International Monetary Fund, or IMF 2012). Despite this growth, poverty in the country remains high; with half of the population living below the national poverty line. The country is also highly heterogeneous, with large socioeconomic differences across states and across urban and rural areas. In 2010, while the extreme poverty ratio in the Federal District and the states of Colima and Nuevo Leon was below 3 percent, in Chiapas, Guerrero, and Oaxaca it was 25 percent or higher. These large regional differences are also found in other indicators of well-being, such as years of schooling, housing conditions, and access to social services. This case study assesses key features and achievements of the Social Protection System in Health (Sistema de Proteccion Social en Salud) in Mexico, and particularly of its main pillar, Popular Health Insurance (Seguro Popular, PHI). It analyzes the contribution of this policy to the establishment and implementation of universal health coverage in Mexico. In 2003, with the reform of the General Health Law, the PHI was institutionalized as a subsidized health insurance scheme open to the population not covered by the social security schemes. Today, the PHI covers all of its intended affiliates, about 52 million people